PELATIHAN BRANDING SEKOLAH PADA SOSIAL MEDIA DI SMP IT MADANI - Wenni Syafitri; Loneli Costaner (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
SMP IT Madani has 10 teachers and 99 students till now. To improve the promotion of SMP IT Madani, various promotional activities have been carried out, one of which is the expo. Evaluation mechanism is not done optimally for promotion. Inappropriate promotion mechanism and evaluation that is not optimal, so that it will impact on school branding. Branding is a mechanism to highlight what is characteristic of the school as well as being a place for school promotion. The target of community service is to realize the school branding training for teachers and school management using information technology to the fullest. This activity has been successfully implemented, step by step carried out carefully. This activity also succeeded in carrying out knowledge transfer activities to our partners, namely SMP IT Madani. Knowledge transferred is how to do effective school branding. The evaluation of this activity is a measurement using the Guttman scale. The evaluation results show success by obtaining a value of 1 for each CS and CR scale.